Phonetic patterns in homophonous Mandarin characters - STEPHEN M. KRAEMER ([Place of publication not identified] : [Publishers name not idntified], 2021)
This book presents phonetic patterns of homophonous characters (characters with the same pronunciation) in Mandarin Chinese.
Keywords: Phonetic; Homophonous Mandarin